EFEKTIVITAS PENERAPAN METODE AT-TAHQIQ TERHADAP KEMAMPUAN PELAFALAN MAKHARIJ AL-HURUF PESERTA DIDIK KELAS I MIN KABUPATEN GOWA - Aris, Nurwahidah; Hamka; Munirah (Prodi PGMI IAI Sahid, 2025)
This research aims to describe 1) Analyzing the form of application of the at-Tahqiq method in class I MIN Gowa Regency, 2) Analyzing students' ability to pronounce makharij al-huruf hijaiyah after implementing the at-Tahqiq method, 3) Analyzing whether the at-Tahqiq method is effective on the ability to pronounce makharij al -Hijaiyah letters in class I MIN Gowa Regency. Data collection methods were carried out through observation and interviews. The research results obtained are 1) The form of applying the at-Tahqiq method in class I MIN Gowa Regency in learning the pronunciation of hijaiyah letters, namely by providing examples of how to pronounce or pronounce the hijaiyah letters properly and correctly, then students are given the opportunity to imitate or re-pronounce them in accordance with examples slowly repeated, 2) Students have shown very good progress as indicated by students being able to pronounce the hijaiyah letters according to the place where the letters come out, 3) The use of the at-Tahqiq method is considered effective in learning the pronunciation of makharijul hijaiyah letters in class I students at MIN Gowa Regency because In applying the at-Tahqiq method, students are able to pronounce the hijaiyah letters well and correctly.